[About CEU - Part 4]
In the context of a conference on the issue of abortion, Associate Professor at CEU’s Political Sciences Department László Bruszt offers an interview about the role of the CEU for the intellectuals in the region. Teaching Philosophy at CEU, Professor János Kis delivers a speech about abortion. Next comes a discussion about the Department of Environmental Sciences & Policy and its multidisciplinary character with Professor Ruben Mnatsakamian. This film contains recordings of a student presenting his paper and being questioned by an evaluation committee. Images of CEU’s buildings, the inner courtyard and the Japanese Garden are presented as well. Interview with Gábor Klaniczay in the Japanese Garden where he explains the origins and the scope of the Medieval Studies Department at CEU also included on this tape.